Revolution and constitutionalism in Britain and the U.S. - Richards, David A. J., author.
1 online resource.
Keywords: "In Revolution and Constitutionalism in Britain and the U.S.: Burke and Madison and Their Contemporary Legacies, David A.J. Richards offers an investigative comparison of two central figures in late 18th century constitutionalism, Edmund Burke and James Madison, at a time when two great constitutional experiments were in play, the Constitution of the Glorious Revolution of 1688 and the U.S. Constitution of 1787. Richards assesses how much, as liberal Lockean constitutionalists, Burke and Madison shared and yet differed regarding violent revolution, offering three pathbreaking and original contributions about Burke's importance. First, the book defends Burke as a central figure in the development and understanding of liberal constitutionalism; second, it explores the psychology that led to his liberal voice, including Burke's own long-term loving relationship to another man; and third, it shows how Burke's understanding of the political psychology of the violence of "political religions" is an enduring contribution to understanding fascist threats to political liberalism from the 18th century onwards, including the contemporary constitutional crises in the U.S. and UK. deriving from populist movements. Mixing thorough research with personal experiences, this book will be an invaluable resource to scholars of political science and theory, constitutional law, political psychology, and LGBTQ+ issues"--